Building Understanding of Facts, Values, and Events in Examining Contemporary Social Phenomena - Fismariza, Wiwi; Fatimah, Siti; Anwar, Syafri (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2026)
This study examines the integration of facts, values, and events in constructing an understanding of contemporary social phenomena, particularly in social science analysis in Indonesia. The main problem of this research stems from the research gap that separates these elements, resulting in less holistic analysis of phenomena such as structural poverty and educational fraud in the post-truth era. Using descriptive qualitative methods through literature research, content analysis, and hermeneutics, this study explores the relationship between these three concepts based on secondary data from scientific literature, journals, and BPS 2025 documents. The results show that facts as empirically verified objective realities, values as subjective views that shape behavior, and events as social dynamics are interrelated, forming a comprehensive analytical framework. For example, poverty data of 8.47% in March 2025 (BPS) is interpreted through the value of injustice as events such as demonstrations, avoiding the reduction of social reality to mere data. This integration is relevant for overcoming information manipulation and supporting social policies that are sensitive to cultural contexts. This thinking is relevant in the context of social education through the application of integrative analysis that encourages students' critical understanding of contemporary phenomena. Although conceptual in nature with limited secondary sources, the results open the way for empirical studies that test this framework in the field. Thus, the integrative legacy of facts-values-events affirms the importance of balancing empirical objectivity, value interpretation, and event dynamics in the advancement of contemporary social science.